Design and Implementation of LCG-Trivium Key Stream Generator into FPGA - Tchahou Tchendjeu A. E; Tchitnga Robert; Fotsin Hilaire B (International Journal of Reconfigurable and Embedded Systems (IJRES), 2018)
This paper presents the Design and implementation into Field ProgrammableGate Array (FPGA) of a combine stream cipher and a simple linear congruential generator circuit to produce key stream. The LCG circuit is used to produce initialization vector (IV) each 264 clock cycle to the cipher trivium in other to strengthen the complexity of the cipher to known attacks on trivium. The LCGTrivium is designed to generate 2144 bits of keystream from an 80-bits secret and a variable 80-bits initial value. To implement the LCG-Trivium on FPGA, we use VHDL to build a simple LCG and Trivium and a state machine to synchronize the functioning of the LCG and Trivium. The number of gates, memory and speed requirement on FPGA is giving after analysis. The design is simulated, synthesized and implemented in Quartus II 10.1, ModelSim-Altera 6.5 and Cyclone IV E EP4CE115F29C7N.